The Ethnomahematics Exploration in the Traditional Game of Sipak Rago - Rina Febriana; Prihastini Oktasari Putri; Ika Septi Hidayati (Edumatika : Jurnal Riset Pendidikan Matematika, 2022)
Education and culture cannot be separated in daily life. Ethnomathematics exists to bridge the gap between culture and education, especially in mathematics. Humans are unaware of activities that use basic mathematical concepts and ideas like counting, measuring (length, area, volume, and weight), number construction, games, and buying-selling activities. This study examines and analyzes the Minangkabau traditional games in the scope of geometry. This research is exploratory research with an ethnographic approach. The subjects of this study were 6 players of the Sipak Rago game. The data was collected through observation, documentation, and interview to find mathematical concepts in the Sipak Rago game. Based on the research, there are mathematical concepts in the Sipak Rago game like the concept of circle elements, circle circumference formula, circle area formula, and angle on a circle.